Exposure to and adoption of family planning information on social media among female civil servants in Ibadan, Nigeria. (2020)
Social media are known to modify health behavior and encourage health improvement. In spite of these, the potential role played by the social media in the acquisition of knowledge and adoption of family planning methods, however, is unclear. This study, therefore, investigated exposure to social media family planning information and adoption of family planning methods among female civil servants in Ibadan, Nigeria. Survey and in-depth interview (IDI) were employed as research designs for the study while uses and gratification theory and health belief model (HBM) provided the theoretical underpinnings. Multistage sampling technique (stratified, simple random and purposive sampling procedures) was adopted in the selection of 232 respondents and 20 interview participants who were within reproductive age (18-45) who participated in the study. Questionnaire and IDI guide were used to generate the data. Quantitative data were analyzed using descriptive statistics (expressed in simple percentages, frequency counts) and chi-square while qualitative data were transcribed and direct quotations that represented the participants’ opinions were used for a Constant comparative analysis. Key findings revealed good knowledge of family planning methods among the respondents but an insignificant relationship between respondents’ exposure to social media information about family planning and their knowledge about family planning methods. Finally, the finding that showed poor adoption of family planning methods among the spondents calls for urgent need for Federal and State Ministries of health, non-governmental organization (NGOs) and other donor agencies to engage in aggressive campaign in order to promote the adoption of effective family planning methods among Nigerian women.